Geology and U-Pb detrital zircon geochronology coupled with zircon fission tracks of the Jauru formation of Parecis Basin, Brazil - Menoncello, Kéttilin Diane; Curvo, Eduardo Augusto Campos; Ruiz, Amarildo Salina; Pavanetto, Pamela; Arinos, Natali Félix; Saenz, Carlos Alberto Tello [UNESP]; Resende, Rosana Silveira [UNESP]; Pimentel, Marcio Martins; de Lima, Gabrielle Aparecida (Elsevier, 2021)
The Jauru Formation fills a symmetric NNW-trending graben whose basement is represented by Calymmian granitic intrusions and the paleoprotorezoic and mesoproterozoic metavolcanic sequence of the Jauru Terrane. The graben represents an intracratonic basin with glacial siliciclastic sequence dominated by lake sediments consisting of conglomerates, fine sandstones, siltstones and shales. The Late Carboniferous timing of basin filling is suggested by Cristatisporites sp. palynomorphs. The detrital zircons U-Pb data shows several ages, highlighting the source areas at 0.9 Ga (Sunsás and Aguapeí Belts), 1.3 Ga (Paraguá Terrane), 1.4 Ga (Rio Alegre and Jauru Terranes), 1.5 Ga (Jauru Terrane), and 1.8 Ga (Jauru and Paraguá Terranes), as well as ages in the Neoarchean (~2.8 Ga) and Siderian (2.1 Ga). The spectrum of U-Pb ages in detrital zircons of the Jauru Formation shows that the ages of the zircons are much older than the Mississippian age of basin formation, suggesting that the Jauru Formation was generated in an extensional continental setting without magmatism. Data from detrital zircon FTM suggest at least three continental exhumation or heating/cooling cycles related to long-lived Pangea break-up. The second and more representative cycle is probably coeval to continental flood basalts of Anari and Tapirapuã Formation, during Upper Triassic and Lower Jurassic. The first (280 Ma) and third (150 Ma) events, are not clearly related to regional or continental geological processes in the South American Platform interior.
Keywords: Continental break-up; Jauru formation; Provenance; Zircon fission tracks; Zircon U-Pb